2023
DOI: 10.14202/vetworld.2023.509-517
|View full text |Cite
|
Sign up to set email alerts
|

Distribution analysis of tetracycline resistance genes in Escherichia coli isolated from floor surface and effluent of pig slaughterhouses in Banten Province, Indonesia

Abstract: Background and Aim: Slaughterhouses and their effluents could serve as a "hotspot" for the occurrence and distribution of antibiotic-resistant bacteria in the environment. This study aimed to understand the distribution of tetracycline resistance genes in Escherichia coli isolated from the floor surface and effluent samples of pig slaughterhouses in Banten Province, Indonesia. Materials and Methods: Ten samples, each from floor surface swabs and effluents, were collected from 10 pig slaughterhouses in Banten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…tetX and tetO were the most common genes in the solid waste samples with prevalences of 100% and 75%, respectively, whereas the prevalence of tetA , tetM , tetO , and tetX in wastewater samples was 50%. The previous studies also reported that tetA was dominantly detected in pig feces (44.9% [ 43 ] and 94.7% [ 44 ]), pig farm waste (66.7% [ 45 ]), pig slaughterhouse wastewater (50% [ 37 ]), and the environment (88.9% [ 44 ] and 100% [ 45 ]). Plasmid-mediated tetX (variant tetX4 ) was detected in E. coli from samples of pig feces (31.03%), pig anal swabs (37.93%), farm environments such as water (6.89%), soil (6.89%) [ 46 ], dust (0.9%) [ 47 ], and pig slaughterhouses [ 48 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…tetX and tetO were the most common genes in the solid waste samples with prevalences of 100% and 75%, respectively, whereas the prevalence of tetA , tetM , tetO , and tetX in wastewater samples was 50%. The previous studies also reported that tetA was dominantly detected in pig feces (44.9% [ 43 ] and 94.7% [ 44 ]), pig farm waste (66.7% [ 45 ]), pig slaughterhouse wastewater (50% [ 37 ]), and the environment (88.9% [ 44 ] and 100% [ 45 ]). Plasmid-mediated tetX (variant tetX4 ) was detected in E. coli from samples of pig feces (31.03%), pig anal swabs (37.93%), farm environments such as water (6.89%), soil (6.89%) [ 46 ], dust (0.9%) [ 47 ], and pig slaughterhouses [ 48 ].…”
Section: Discussionmentioning
confidence: 96%
“…This significantly high prevalence was attributable to the use of E. coli as a commensal bacterium and the potential of the microbe to cause various digestive tract disorders and other extra-intestinal diseases. Furthermore, this bacterium is widespread and abundant in pig farms [ 12 ], pig slaughterhouses [ 37 ], and the surrounding environment [ 16 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the transmission of resistance genes from pigs to the environment, posing a significant public health threat. Another study found that several ARGs were widely present, especially tetA and tetM , with the highest detection rates in samples derived from a wastewater treatment plant in Guangzhou [ 76 ].…”
Section: Types Of Args In Aquatic Environmentmentioning
confidence: 99%
“…Tet(X)-producing bacteria carry the tet(X) gene, which encodes a flavin-dependent monooxygenase enzyme that can inactivate tetracyclines. Examples of bacteria that produce Tet(X) include Bacteroides fragilis , Escherichia coli , and Acinetobacter baumannii [ 97 , 98 , 99 , 100 , 101 ]. Tet(M)-producing bacteria carry the tet(M) gene, which encodes a ribosomal protection protein that can protect the bacterial ribosome from the inhibitory effects of tetracyclines.…”
Section: How Can the Gut Microbiome Alter Tetracycline Treatment?mentioning
confidence: 99%